A dual‐luciferase reporter system for characterization of small RNA target genes in both mammalian and insect cells. (1st November 2021) - Deng, Zhongyuan; Zhang, Yuting; Li, Leyao; Xie, Xingcheng; Huang, Jinyong; Zhang, Min; Ni, Xinzhi; Li, Xianchun
Abstract: MicroRNAs (miRNAs) are regulatory RNA molecules that bind to target messenger RNAs (mRNAs) and affect the stability or translational efficiency of the bound mRNAs. Single or dual‐luciferase reporter systems have been successfully used to identify miRNA target genes in mammalian cells. These reporter systems, however, are not sensitive enough to verify miRNA–target gene relationships in insect cell lines because the promoters of the target luciferase (usually Renilla ) used in these reporter systems are too weak to drive sufficient expression of the target luciferase in insect cells. In this study, we replaced the SV40 promoter in the psiCHECK‐2 reporter vector, which is widely used with mammalian cell lines, with the HSV‐TK or AC5.1 promoter to yield two new dual‐luciferase reporter vectors, designated psiCHECK‐2‐TK and psiCHECK‐2‐AC5.1, respectively. Only psiCHECK‐2 and psiCHECK‐2‐AC5.1 had suitable target ( Renilla )/reference (firefly) luciferase activity ratios in mammalian (HeLa and HEK293) and insect (Sf9, S2, Helicoverpa zea fat body and ovary) cell lines, while psiCHECK‐2‐TK had suitable Renilla /firefly luciferase activity ratios regardless of the cell line. Moreover, psiCHECK‐2‐TK successfully detected the interaction between Helicoverpa armigera miRNA9a and its target, the 3′‐untranslated region of heat shock protein 90, in both mammalian and H. zea cell lines, but psiCHECK‐2 failed to do so in H. zea cell lines. Furthermore, psiCHECK‐2‐TK with the target sequence, HzMasc ( H. zea Masculinizer ), accurately differentiated between H. zea cell lines with or without the negative regulation factor (miRNA or piRNA) of HzMasc . These data demonstrate that psiCHECK‐2‐TK can be used to functionally characterize small RNA target genes in both mammalian and insect cells. Abstract : We replaced the pSV40 promoter of the widely used psiCHECK‐2 reporter vector with the pHSV‐TK and pAC5.1 promoter, yielding a dual‐luciferase reporter vector, designated as psiCHECK‐2‐TK and psiCHECK‐2‐AC5.1. Relative to psiCHECK‐2, psiCHECK‐2‐TK and psiCHECK‐2‐AC5.1 had significantly higher Renilla luciferase activity and Renilla /firefly activity ratio in H. zea fat body, ovary, Sf9 and S2 cell lines. Test application showed that psiCHECK‐2‐TK successfully detects the interaction between Helicoverpa armigera miRNA9a and its target hsp90 3'‐UTR in both mammalian cell and H. zea cell lines. Furthermore, transfection of the construct psiCHECK‐2‐TK‐HzMasc ( H. zea masculinizer masc ) accurately revealed the presence of a negative regulation factor (miRNA or piRNA) for Masc in H. zea ovary cell line.